Ancient Tangut manuscripts rediscovered - van Driem, George (2024)
It is a cause for great joy that, since the appearance of the article by van Driem and Kepping (1991), the original Tangut manuscripts bearing interlinear Tibetan transcriptions, which had been lost for decades, have now been found and returned to the Institute of Oriental Studies in St. Petersburg. These ancient manuscripts of inestimable scholarly value were returned to the Institute of Oriental Studies in October, 1991, after the unsuccessful coup attempt of August 19-21, 1991, and the subsequent preventive expurgation of KGB files by its own agents.